Absence of SLC2A1 Mutations Does Not Exclude Glut1 Deficiency Syndrome - Klepper, Joerg (Neuropediatrics, 2013)
Increasingly, the absence of SLC2A1 mutations causes pediatricians to abandon the diagnosis of Glut1 deficiency. For several reasons this is not justified. Potential disease mechanisms in SLC2A1-negative Glut1 deficiency are discussed.
Keywords: glut1 deficiency; SLC2A1; ketogenic diet